Инновационная восприимчивость рынка для отрасли электроэнергетика - Дюжев, Виктор Геннадиевич; Бойченко, Олег Игоревич (Придніпровська державна академія будівництва та архітектури, 2018)
Статья посвящена теоретическому рассмотрению методик расчета емкости рынка для отрасли электроэнергетики. Осуществлены примеры расчета для украинского рынка и других рынков СНГ. Рассмотрены вопросы расчетов емкости рынка. Определение справедливой емкости рынка является одной из проблем современных корпоративных финансов, данные методики расчета в первую очередь будут полезны для них.

The article is devoted to the theoretical consideration of methods for calculating the market capacity for the electric power industry. Examples of calculations for the Ukrainian market and other CIS markets are provided. The issues of market capacity calculations are considered. Determining the fair market capacity is one of the problems of modern corporate finance, these methods of calculation are primarily useful for them.
Innovative susceptibility of the market for industry electric power engineering
Keywords: емкость рынка; электроэнергетика; мультипликаторы; market capacity; electric power industry; multipliers